Coordinates of Contemporary Exegesis in Contemporary Sequential Exegesis - Parivash Hosseinpour; Saeed Abbasinia; Sayyed Hesamodin Hosseini (آموزه‌های قرآنی)
Contemporary interpretation is one of the most important interpretive approaches, the origin of which is to present the messages of the Qur'an in accordance with the requirements of the time and the needs of the day. One of the issues that seems necessary to address is the study of its coordinates in various interpretive formats; examining the coordinates of modern exegesis in a specific format or interpretations of a specific period of time, as it can be useful in understanding the nature of this approach, to know the position, role and effectiveness of this approach in that interpretive format is also effective. Despite the importance of addressing this issue and the important place of this approach in the field of exegesis, especially contemporary exegesis, this issue has not been considered and addressed so far. From this perspective, in this research, an attempt has been made to examine the question by examining contemporary sequential interpretations: What are the characteristics of contemporary interpretation in contemporary sequential interpretations? According to the research findings, which has been done by using qualitative content analysis method and studying contemporary interpretive sources, contemporary exegesis is an approach in which the commentator tries to interpret the Qur'an in accordance with the needs, conditions and requirements of his time. Hence, in the contemporary period, the motives, knowledge and expertise of the commentators, the demands and needs of the time, social, political and cultural changes and intellectual issues and controversies of this period, have caused the emergence of a special aspect of modern interpretation in sequential interpretations that has features and characteristics such as: emphasizing the thematic unity of the verses of each surah, systematizing the verses, exemplary development of the verses, answering emerging issues and dubious things, and paying attention to persuading the audience.